PEMENUHAN GANTI RUGI DAN/ATAU MELAKUKAN TINDAKAN TERTENTU ATAS KERUSAKAN LINGKUNGAN HIDUP OLEH PT. GREENFIELDS FARM 2 BLITAR - Ramadhan Kahfi Fahlafi; Hervina Puspitosari (Gapenas Publisher, 2023)
A healthy environment is a human right that is guaranteed by the 1945 Constitution of the Republic of Indonesia. Law of the Republic of Indonesia Number 32 of 2009 concerning the Protection and Management of the Environment gives the government and/or local government, communities and environmental organizations the right to file a claim for compensation. losses from pollution and/or environmental damage. This is in accordance with the principles of environmental law, namely the polluter pays principle. This study aims to find out how to fulfill compensation and/or take certain actions for environmental damage by PT. Greenfields Farm 2 Blitar and what are the inhibiting factors in fulfilling compensation and/or taking certain actions by PT. Greenfields Farm 2 Blitar. This study uses empirical juridical research methods. Data collection was carried out by means of literature studies and interviews. Data analysis was carried out using descriptive analytical methods and using a qualitative approach. The results of the study show that there is a reference in calculating the amount of compensation that can only be determined by an expert on the basis of the Minister of Environment Regulation Number 7 of 2014 concerning Environmental Losses Due to Pollution and/or Environmental Damage. In fulfilling compensation and/or taking certain actions there are 3 (three) inhibiting factors in fulfilling compensation for environmental pollution and/or damage, namely legal factors such as the absence of a clear legal basis to calculate the valuation of compensation for the community due to environmental damage, law enforcement factors such as the absence of a deterrent effect in imposing administrative sanctions, and societal factors such as a lack of awareness of the importance of the environment